Epigenetic impacts of maternal tobacco and e-vapour exposure on the offspring lung - Razia Zakarya; Ian Adcock; Brian G. Oliver (Clinical Epigenetics, 2019)
Abstract In utero exposure to tobacco products, whether maternal or environmental, have harmful effects on first neonatal and later adult respiratory outcomes. These effects have been shown to persist across subsequent generations, regardless of the offsprings’ smoking habits. Established epigenetic modifications induced by in utero exposure are postulated as the mechanism underlying the inherited poor respiratory outcomes. As e-cigarette use is on the rise, their potential to induce similar functional respiratory deficits underpinned by an alteration in the foetal epigenome needs to be explored. This review will focus on the functional and epigenetic impact of in utero exposure to maternal cigarette smoke, maternal environmental tobacco smoke, environmental tobacco smoke and e-cigarette vapour on foetal respiratory outcomes.